2016
DOI: 10.1002/jcph.826
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Analysis of Subcutaneous Tocilizumab in Patients With Rheumatoid Arthritis From 2 Randomized, Controlled Trials: SUMMACTA and BREVACTA

Abstract: Tocilizumab is a humanized anti–interleukin‐6 receptor antibody for treating rheumatoid arthritis. Pharmacokinetic/pharmacodynamic analysis was performed on the 24‐week double‐blind parts of 2 randomized, controlled trials: SUMMACTA and BREVACTA. SUMMACTA compared subcutaneous tocilizumab 162 mg every week to intravenous tocilizumab 8 mg/kg every 4 weeks, whereas BREVACTA evaluated 162 mg subcutaneous tocilizumab every 2 weeks versus placebo. In addition to noncompartmental analysis, a 2‐compartment population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 18 publications
4
49
1
2
Order By: Relevance
“…During the MUSASHI open-label period, patients with an inadequate response to TCZ-SC q2w could have their dosing interval shortened and receive TCZ-SC qw, which resulted in increased TCZ serum trough levels and improved efficacy with a comparable safety profile [12]. In pharmacokinetic and pharmacodynamic analyses of TCZ-SC in patients from the SUMMACTA and BREVACTA trials, body weight was an important covariate affecting clearance and volume of distribution; the observed mean TCZ trough levels for patients !100 kg were lower with TCZ-SC q2w compared with TCZ-SC qw [13]. Together, these results suggest that patients with an inadequate response to TCZ-SC q2w and low TCZ serum trough levels may benefit from a shortened dosing interval [11][12][13].…”
Section: Introductionmentioning
confidence: 80%
“…During the MUSASHI open-label period, patients with an inadequate response to TCZ-SC q2w could have their dosing interval shortened and receive TCZ-SC qw, which resulted in increased TCZ serum trough levels and improved efficacy with a comparable safety profile [12]. In pharmacokinetic and pharmacodynamic analyses of TCZ-SC in patients from the SUMMACTA and BREVACTA trials, body weight was an important covariate affecting clearance and volume of distribution; the observed mean TCZ trough levels for patients !100 kg were lower with TCZ-SC q2w compared with TCZ-SC qw [13]. Together, these results suggest that patients with an inadequate response to TCZ-SC q2w and low TCZ serum trough levels may benefit from a shortened dosing interval [11][12][13].…”
Section: Introductionmentioning
confidence: 80%
“…TCZ-SC was given at a fixed dose, and patients with a higher BMI may fail to maintain serum trough concentrations of TCZ required for a response. Previous studies showed that following a switch from TCZ-IV every 4 weeks to TCZ-SC every 2 weeks, patients with higher body weight had reduced TCZ serum trough concentrations and reduced efficacy [18,26].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, population PK analyses of 75 patients with sJIA and 188 patients with pJIA have been conducted to determine the PK of TCZ-IV in these patients (F. Hoffmann-La Roche Ltd., data on file). We have summarized the PK profiles in Table 1 [37,72,73]. PK exposure parameters for TCZ were found to be similar between healthy individuals and patients with RA, indicating that even the presence of active disease does not impact the PK profile of TCZ [74].…”
Section: Safety Pharmacokinetics and Immunogenicitymentioning
confidence: 99%
“…However, patients treated with TCZ should be monitored for malignancies to provide data that can be used for to assess risk over the longer term. The data for the pharmacokinetics (PK) of TCZ-IV and TCZ-SC are based on population PK analyses of 1793 and 1759 patients with RA, respectively [72][73][74]. In addition, population PK analyses of 75 patients with sJIA and 188 patients with pJIA have been conducted to determine the PK of TCZ-IV in these patients (F. Hoffmann-La Roche Ltd., data on file).…”
Section: Safety Pharmacokinetics and Immunogenicitymentioning
confidence: 99%